S11-4. Deviance-related responses along the auditory hierarchy in the brain. Issue 5 (May 2018) - Shiga, Tetsuya; Escera, Carles; Yabe, Hirooki
Abstract : In electrophysiological research, automatic auditory deviance detection has traditionally been associated with mismatch negativity (MMN), a component of the auditory evoked potential (AEP), peaking at 100–250 ms from stimulus onset. However, a series of recent studies have revealed that MMN may no longer represent the earliest electrophysiological response of auditory change detection in human, as shown by deviant modulated middle latency responses (MLRs), peaking at latencies 20–50 ms after stimulus onset. Recently, early correlates of deviance detection can be seen in the frequency following response (FFR), a sustained component of the auditory brainstem potential that is phase-locked to the periodic characteristics of the eliciting stimulus. Here, amplitude modulated sounds were presented to healthy subjects in a frequency oddball paradigm, and deviance-related responses were elicited in the FFR and MLR, as well as the long latency response (LLR), reflected by MMN. These findings demonstrate that different levels along the auditory hierarchy show auditory deviations from a regular sound sequence in one single recording protocol.